Influence of supply chain risk management and its mediating role on supply chain performance of fresh fruit and vegetable agropreneurs in Malaysia - Waqas, Umair (2020)
Agropreneurs of fresh fruits and vegetables are important contributors to the economy; as such, supply chain risk management is an important area for the survival and growth of agropreneurs. Compared to the industrial sector, the agricultural sector is exposed to more unpredictable risks and uncertainties. Thus, risk management is critical to the success of agri-fresh businesses. The main objective of this research was to examine the mediating effect of supply chain risk management to reduce the impact of supply chain risks and to increase supply chain performance among smallholder agropreneurs in Malaysia. In addition, this study examined the moderating role of knowledge management between supply chain risks and supply chain risk management. The quantitative survey method was used to collect data from 430 agropreneurs in five states in Malaysia. PLSSEM was used to analyse the data. The results confirmed that supply chain risks are negatively associated with supply chain performance. Further, the risk assessment and risk mitigation aspects of risk management were found to mediate the relationship between supply chain risks and supply chain performance, while risk identification did not have a mediating effect on this relationship. Additionally, knowledge management was found to moderate the relationship between supply chain risks and two aspects of risk management, i.e. risk identification and risk assessment, but did not have a moderating effect between supply chain risks and risk mitigation. The results of the present study provide useful insights regarding supply chain risks, supply chain risk management, knowledge management, and supply chain performance of small agropreneurs of fresh fruits and vegetables in Malaysia. These findings can be vital for government institutes to better understand the value of supply chain risk management practices towards the overall performance of agropreneurs. Additionally, the results of this study urge agropreneurs to have a close understanding with government institutions so they can learn and effectively adapt supply chain risk management. As the present study employed the quantitative method, it is suggested to conduct a study with the mixed-method approach for an in-depth explanation of the issues discussed in the present study. For fresh fruits and vegetables, the environment may not be the same during different stages of the crop cycle. Therefore, a longitudinal study might also be more suitable for future research to understand the whole process.